Isolation and Identification of Antibiotic-Producing Halophilic Bacteria from Dagh Biarjmand and Haj Aligholi Salt Deserts, Iran - Babak Elyasifar; Sevda Jafari; Somayeh Hallaj-Nezhadi; Florence Chapeland-leclerc; Gwenaël Ruprich-Robert; azita dilmaghani (Tabriz University of Medical Sciences, 2019)
Background: Halophilic bacteria are potent organisms in production of novel bioactive antimicrobial compounds which might be considered in drug innovation and control of plant pathogens. Salt deserts in Semnan province are of the most permanent hypersaline areas in the North of Iran. Despite the importance of these areas, there is no scientific report regarding the biodiversity and potency of their halophilic bacteria. Thus, aforementioned areas were selected to detect the halophilic bacteria. Methods: Here, seven strains were isolated and cultured on their molecular and biochemical properties were characterized. To determine the antibiotic potency of the isolates, agar well diffusion method was conducted. Phylogenetic analysis was done to reveal the isolates relationship with previously known strains. Results: As a result, growth of the strains in the medium containing 5 to 20% (w/v) NaCl determined that the majority of the isolates were moderately halophile. Catalase activity of all strains was positive. The results represented that D6A, Dar and D8B have antimicrobial effects against different plant and human pathogens. Phylogenic tree analysis also showed that two strains of D6A and Dar are belonged to Bacillus subtilis and D8B is belonged to Virgibacillus olivae. The bacteria extracts were evaluated for their antifungal and antibacterial activities on human and Plant pathogenic strains. The MIC of the extract B. subtilis against was found active against human pathogenic fungi and Plant pathogenic bacteria and fungi, ranging from 12.5 to 25 µg/mL. Conclusion: This study highlights the therapeutic and prophylactic potential of B. subtilis extracts as antibacterial and antifungal agents.